(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2012)
The main goal of the present work is to summarize the Relational Frame Theory (RFT) account of ana-logical reasoning, reviewing theoretical models and experimental studies published so far. Additionally, developmental studies of analogical reasoning during childhood will be addressed, considering the alternative hypothesis and controversies between different psychological theories. Findings from cognitive studies using neuroimaging techniques will also be discussed. Finally, the potential applications of the paradigm will be considered. The studies reviewed about analogical reasoning from the RFT provide relevant empirical evidence, mainly in the field of assessment and suggest advantages of this paradigm compared to cognitivist approaches. In turn, its implementation is proposed as a tool for cognitive training. In conclusion, the RFT offers a useful model to study analogical reasoning from the behavior analysis perspective.